An interpretation of the genetic polymorphism and population genetic background of Ankang Han population via a novel InDel panel - Wei Cui; Xiaoye Jin; Yating Fang; Qiong Lan; Jiangwei Lan; Man Chen; Shuyan Mei; Tong Xie; Bofeng Zhu (Forensic Sciences Research, 2021)
In this research, genotyping data of 43 InDel loci in 311 Han individuals in Ankang city, Shaanxi province, China were detected using a self-developed five-dye multiplex amplification panel. The allelic frequencies and forensic parameters of all InDel loci were calculated. The combined power of discrimination and probability of exclusion values were 0.999 999 999 999 999 998 827 39 and 0.999 887 424, respectively, which demonstrated that this 43-InDel panel was powerful for individual identifications in Ankang Han population. Moreover, genetic distances, pairwise FST values, principal component analyses, phylogenetic trees and STRUCTURE analyses were performed to investigate the genetic affinities between Ankang Han and reference groups. Population genetic investigations indicated that Ankang Han population had a close genetic relationship with Southern Han population compared with other reference groups.